Suppression of Somatosensory Evoked Cortical Responses by Noxious Stimuli - Takeuchi, Nobuyuki (Brain Topogr, 2019)
Paired-pulse suppression refers to attenuation of neural activity in response to a second stimulus and has a pivotal role in inhibition of redundant sensory inputs. Previous studies have suggested that cortical responses to a somatosensory stimulus are modulated not only by a preceding same stimulus, but also by stimulus from a different submodality. Using magnetoencephalography, we examined somatosensory suppression induced by three different conditioning stimuli. The test stimulus was a train of electrical pulses to the dorsum of the left hand at 100 Hz lasting 1500 ms. For the pulse train, the intensity of the stimulus was abruptly increased at 1200 ms. Cortical responses to the abrupt intensity change were recorded and used as the test response. Conditioning stimuli were presented at 600 ms as pure tones, either innocuous or noxious electrical stimulation to the right foot. Four stimulus conditions were used: (1) Test alone, (2) Test + auditory stimulus, (3) Test + somatosensory stimulus, and (4) Test + nociceptive stimulus. Our results showed that the amplitude of the test response was significantly smaller for conditions (3) and (4) in the secondary somatosensory cortex contralateral (cSII) and ipsilateral (iSII) to the stimulated side as compared to the response to condition (1), whereas the amplitude of the response in the primary somatosensory cortex did not differ among the conditions. The auditory stimulus did not have effects on somatosensory change-related response. These findings show that somatosensory suppression was induced by not only a conditioning stimulus of the same somatosensory submodality and the same cutaneous site to the test stimulus, but also by that of a different submodality in a remote area.